IMPLEMENTASI UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DI KOTA SAMARINDA - Linda Astuti (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT      The family is the smallest social unit in society that act and a great impact on the development of social and personal development of each member of the family. Families need their own organizations and the need to head households as important figures who lead the family.      Domestic violence can happen to a husband, wife, and children, and those in the domestic sphere is a difficult problem to overcome. Generally, people assume that it belongs to the family members of the man and the problem of domestic violence is a private matter that can not be interfered with by others. While the legal system and social culture that exists when it does not guarantee protection of victims of domestic violence.       Factors that lead to domestic violence in the city of Samarinda is poverty / economy, unstable psychological state actors, and the wrong perception of looking at the problem of domestic violence. Of these factors, the main factors that lead to domestic violence in the city of Samarinda is poverty / economic pressure. It takes the rigor of law enforcement officials in handling cases of domestic violence in the city of Samarinda to actually implement existing sanctions under Law No. 23 of 2004 on the elimination of domestic violence to be able to pose a deterrent for the